2018
DOI: 10.2147/cia.s166423
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age on effect-site concentration of remifentanil for suppressing anesthetic emergence cough in male patients undergoing laparoscopic cholecystectomy

Abstract: BackgroundRemifentanil infusion during emergence lowers cough. Effect-site concentration (Ce) of remifentanil using target-controlled infusion (TCI) has been evaluated in previous studies. Recent studies revealed the existence of sex-related differences in remifentanil Ce in young and elderly patients. Thus, there was the need to re-evaluate the effect of age in single sex. We investigated the remifentanil Ce for suppressing emergence cough in young and elderly male patients and evaluated the age-related diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
3
1
Order By: Relevance
“…We found no differences in sex, age, BMI, smoking, or and drinking status among the 3 different groups of ABCB1 rs1045642 genotypes. This is similar to the results of studies conducted by other scholars, which also showed that patient sex, age, BMI, smoking, and drinking have no influence on the pharmacodynamics of Remifentanil [15,16]. Hence, it is believed that the sex, age, BMI, smoking, and drinking in this study did not affect the efficacy of Remifentanil, and its dose does not need to be adjusted in different ABCB1 rs1045642 genotype groups according to the sex age, BMI, smoking, and drinking status of the patients.…”
Section: Discussionsupporting
confidence: 90%
“…We found no differences in sex, age, BMI, smoking, or and drinking status among the 3 different groups of ABCB1 rs1045642 genotypes. This is similar to the results of studies conducted by other scholars, which also showed that patient sex, age, BMI, smoking, and drinking have no influence on the pharmacodynamics of Remifentanil [15,16]. Hence, it is believed that the sex, age, BMI, smoking, and drinking in this study did not affect the efficacy of Remifentanil, and its dose does not need to be adjusted in different ABCB1 rs1045642 genotype groups according to the sex age, BMI, smoking, and drinking status of the patients.…”
Section: Discussionsupporting
confidence: 90%
“…After adjustment for these factors, age was still an independent factor. From the perspective of the increased sensitivity of the elderly to anesthetics, our results do not conflict with previous studies ( Akhtar, 2018 ; Kim et al, 2018 ; Sahinovic et al, 2018 ; You et al, 2019 ). However, unlike previous research paradigms, we focused on elderly surgical population which aged over 65 years, and tried to eliminate the interference caused by concomitant medication, comorbidities and renal insufficiency.…”
Section: Discussioncontrasting
confidence: 56%
“…On the other hand, Lee et al showed that both the Ce of propofol at 2.9 ± 0.7 mcg/ml (to keep BIS levels between 40 and 50), and the Ce of remifentanil were higher than our results during skull pin fixation, it might be due to age/gender-related differences in the Ce of propofol/remifentanil based on our majority of older female patients 24 , 32 . However, age might not affect the Ce of remifentanil during surgery 33 . Further studies are needed for checking effects of age and gender to Ce of propofol/remifentanil.…”
Section: Discussionmentioning
confidence: 99%